Development of public monitoring of land relations - Novakovskyi, L.; Novakovska, I. (Land Management, Cadastre and Land Monitoring, 2023)
The Constitution of Ukraine, recognizing the indispensability of land as a natural resource, rightfully acknowledges it as the country’s primary national wealth, deserving special protection by the state. On May 12, 2023, the Cabinet of Ministers of Ukraine approved the Procedure for conducting public monitoring of land relations and land market monitoring. From 1993 to 2017, in accordance with existing legislation, land and soil monitoring have been carried out in Ukraine as components of environmental monitoring. It is practically considered that there is one main direction of land monitoring - land monitoring, although terms such as "land monitoring," "land monitoring," "monitoring of land resources," "soil monitoring," "land use monitoring," "agricultural land use monitoring," etc., are used in scientific literature. These monitoring activities had an ecological focus, serving to preserve one of the ecosystems - land resources - and mitigate environmental crises. However, these monitoring efforts were mainly unsystematic and scattered, which limited their application in addressing urgent socio-economic and environmental issues related to land use. The standard state of monitoring of this resource in 2017 shifted towards monitoring land relations and has now acquired the status of public monitoring of the land market starting from 2023, representing the quintessence of market-based land relations in the country. The essence of public monitoring is not only a political vestige but also the essence of market-based land relations that have developed in Ukraine. This highlights not only the environmental role of land monitoring but, above all, emphasizes its socio-economic significance in the functioning of market-based land relations. [1] The ordinary state of monitoring a specified resource in 2017 became monitoring of land relations, and starting from 2023, it acquired the status of public monitoring of the land market, representing the essence of market land relations in the country. The essence of public monitoring manifested not only as a political relic but also as the essence of market land relations that have developed in Ukraine. This emphasizes not only the environmental role of land monitoring but, above all, highlights its socio-economic significance in the functioning of market land relations. Keywords: Public monitoring, land market monitoring, environmental monitoring, land use.